Insulin-resistant brain state (IRBS) changes membrane composition of fatty acids in temporal and entorhinal brain cortices of rats: relevance to sporadic Alzheimer’s disease? - Plaschke, Konstanze; Müller, Dorothea; Hoyer, Siegfried (Journal of neural transmission, 2010)
An insulin-resistant brain state (IRBS) was induced by intracerebroventricular application of the diabetogenic substance streptozotocin (STZ) to investigate changes in cerebral fatty acids. Six weeks after the first STZ injection, increases were found in the concentrations of palmitic and stearic acid in temporal cortex; and of palmitic acid in entorhinal cortex indicative of membrane phospholipid breakdown, and damage of the membrane structure. The relevance of these changes is discussed in relation to sporadic Alzheimer’s disease.
Gesehen am 04.05.2023